Fasilitas, Lokasi Dan Daya Tarik Wisata Pada Minat Berkunjung Kembali Ke Objek Wisata Pantai Carocok Painan - Ria Murdani; Lidya Martha (Nawasena: Jurnal Ilmiah Pariwisata, 2023)
This study aims to examine the facilities, locations, and tourist attractions on the intention to return to the tourist object of Carocok Painan Beach. This research is a quantitative study, the sampling method uses incidental sampling techniques with a total of 100 respondents. The data analysis technique used is validity test, reliability test, normality test, multicollinearity test, heteroskeasticity, multiple regression analysis and t test. The results showed that facilities had a negative and not significant effect on intention to return, location had a positive and significant effect on intention to return, and tourist attraction had a positive and significant effect on intention to return.